A Time-Motion Analysis of An Urban Immunization Facility in The Konkan Region of India - Chopade, Rahul; Kamate, Ravikiran Padmakar; Bhaisare, Kalpalata Abhiman (National Journal of Community Medicine, 2022)
Context/Background: Time motion studies involve the collection of data regarding the amount of time necessary to perform a specific movement or task by individuals or groups of people. Thus, hospital administrators can determine how much time is needed to execute that activity and whether the time is used efficiently and whether there is any possibility of improvement. Aims/Objectives: To study the operational efficiency of an immunization clinic attached to the urban health training centre. To assess the perception of patients regarding the health service delivery in the immunization OPD. Methodology: It was an observational study carried out in the immunization clinic of an urban health training center attached to a tertiary medical college, in the Konkan region of India for over 6 months. About 300 patients were included in the study. Results: According to 23.34% of study participants, the total time was too long. 24% of study participants were not satisfied with the total time taken while 48.33% of study participants were satisfied with the total time. Conclusions: Management of time at various levels of the healthcare system is a need for the hour and necessary remedial actions should be initiated for optimal functioning of the healthcare system.